Strategi Peningkatan Keterlibatan Orang Tua Siswa sebagai Mitra dalam Ekosistem Mutu Pendidikan - Hamid, Abdul; Ismail, Benhur; Putra, Ansori Dasa; Purwito, Teguh; Rosidah, Nur (Lentera: Jurnal Ilmiah Kependidikan, 2025)
Parental involvement as an active partner in the educational ecosystem is a critical factor influencing education quality. This study aims to analyze the actual condition of parental involvement, identify barriers and facilitators, and formulate strategies to enhance parental engagement at UPT SMPN 1 Umpu Semenguk, Way Kanan. This research employed a qualitative approach with a case study design conducted in September-October 2025. Data were collected through in-depth interviews with the school principal, vice principals, committee coordinator, guidance counselors, homeroom teachers, and parent representatives, as well as observations of activities involving parents and documentation study of school programs. Data analysis utilized the interactive analysis model of Miles, Huberman, and Saldaña with data triangulation to ensure the credibility of findings. Results indicate that parental involvement remains at the passive participation stage, dominated by financial contributions (85%) and formal attendance (60%), while time contributions and decision-making participation are extremely low. Primary barriers include work commitments (78%), lack of curriculum understanding (65%), and one-way communication (70%), whereas facilitators include principal leadership (85%) and student-related triggers (70%). Recommended strategies encompass enhancing two-way communication, empowering parents as mentor teams and resource persons, relevant parenting training programs, and formal recognition. The proposed partnership ecosystem model adopts Epstein's Framework of Six Types of Involvement with local contextualization to sustainably improve education quality.